Formulation of reference solutions for compaction process in sedimentary basins. (7th August 2020) - Lemos, Paulo Sérgio B.; Brüch, André; Maghous, Samir
Summary: This paper is devoted to the development of semianalytical solutions for the deformation induced by gravitational compaction in sedimentary basins. Formulated within the framework of coupled plasticity–viscoplasticity at large strains, the modeling dedicates special emphasis to the effects of material densification associated with large irreversible porosity changes on the stiffness and hardening of the sediment material. At material level, the purely mechanical compaction taking place in the upper layers of the basin is handled in the context of finite elastoplasticity, whereas the viscoplastic component of behavior is intended to address creep‐like deformation resulting from chemo‐mechanical that prevails at deeper layers. Semianalytical solutions describing the evolution of mechanical state of the sedimentary basin along both the accretion and postaccretion periods are presented in the simplified oedometric setting. These solutions can be viewed as reference solutions for verification and benchmarks of basin simulators. The proposed approach may reveal suitable for parametric analyses because it requires only standard mathematics‐based software for PDE system resolution. The numerical illustrations provide a quantitative comparison between the derived solutions and finite element predictions from an appropriate basin simulator, thus showing the ability of the approach to accurately capture essential features of basin deformation.